Terkendalanya Proses Implementasi Kartu Jakarta Sehat (KJS) - Sudarjah, Gugum Mukdas; Maqin, Abdul (Jurnal Trikonomika, 2013)
Limited access to health care received by the poor citizens in Jakarta during the period of the previous administration to be one of the issues raised by Jokowi-Ahok to attracts the sympathy citizens of Jakarta in the election of Governor and Deputy Governor of the period 2012-2017, through the Jakarta Health Card (KJS) Jokowi Ahok makes serious effort to improve standards for people in the healthcare sector. Problems appear when the Jakarta Health Card program was launched, the citizenâs euphoria towards free treatment creates an impact on increasing patient Jakarta Health Card users. Limitations of medical infrastructure (health centers and Referral Hospital), they cause the disruption of the implementation of public policy in the health sector through the program launched. The purpose of this study was to analyze the problems of implementation of the Jakarta Health Card (KJS) does not function as expected. The method used is to use the approach method Institutional Analisys Development (IAD). The results obtained in this study is the problem of the procurement of Public services does not always work as expected many factors that cause it, in the case of the implementation of the Jakarta Health Card (KJS) constraints derived from the behavior of poor people in treatment as well as medical facilities and infrastructure are available.